KNOWLEDGE MANAGEMENT AS THE BASIS OF QUALITY OF HIGHER EDUCATION - Horban, Oleksander (Educological discourse, 2021)
In this article, the use of the actualization of the problem of the knowledge management process, which is due to the need to mobilize scientific activity, practical implementation of scientific results and improve the quality of higher education. In the latest conditions of the pandemic crisis, there are significant changes in the organization of the culture of knowledge management and quality improvement in the modern system of higher education. The effectiveness of distance learning and distance organization of higher education comes to the fore. This necessitates the improvement of management models of higher education institutions and changes in the functions of key actors in management models. It is concluded that modern knowledge management in the higher education system cannot be limited to the process of knowledge creation, knowledge exchange and their implementation. Currently, the higher education system faces the need to address the impact of knowledge management culture on the performance of individuals, groups and organizations in order to improve the quality of education. The culture of knowledge management is closely linked to the organizational culture of higher education institutions. Within the system of higher education, one can observe different dynamics of development and the relationship between organizational and information culture. Quality management goals in higher education management are usually met by a number of small additional projects. The philosophy of total quality management is essentially large-scale, inspiring and comprehensive, but its practical implementation is carried out in stages and consistently. Effective and long-lasting changes are based on a large series of small and achievable projects.